ASSESSMENT OF THE QUALITY OF LIFE OF PATIENTS WITH DIFFUSE TOXIC GOITER AGAINST THE BACKGROUND OF DRUG THERAPY AND SURGICAL TREATMENT - D.A, Urunbayeva; D.T, Umarova; A.E, Bashirova (PT. Antis International Publisher, 2025)
Objective: This study aims to evaluate the quality of life in patients with diffuse toxic goiter (DTG) undergoing drug therapy and surgical treatment. It also seeks to identify key predictors of complications associated with DTG. Methods: The study involved patients diagnosed with DTG, assessing the prevalence of subclinical and manifest thyrotoxicosis. The analysis focused on the impact of disease duration on complications such as thyrotoxic heart disease, endocrine ophthalmopathy, and toxic hepatitis. Additionally, the quality of life was compared between patients receiving thyroidectomy and those undergoing drug therapy with thyreostatics. Results: Findings indicate that DTG is more prevalent in women than men. Among the patients, subclinical thyrotoxicosis accounted for 66.7%, while manifest thyrotoxicosis was 33.3%. Disease duration was a critical factor in the progression of complications. Patients who underwent timely thyroidectomy exhibited better quality of life outcomes. Physical functioning improved by 23%, while emotional functioning, mental health, and social functioning increased by 40.7%, 22.5%, and 30.7%, respectively, compared to those receiving drug therapy. Novelty: This study highlights the significant role of thyroidectomy in improving the quality of life for DTG patients compared to drug therapy. It also emphasizes the predictive value of disease duration in the development of DTG-related complications, contributing to better clinical decision-making.